A new subspecies of Chlaenius (Chlaeniellus) laeviplaga Chaudoir, 1876 (Coleoptera: Carabidae: Licininae) from South Iran - Azadbakhsh, Saeed; Kirschenhofer, Erich (Zootaxa, 2016)
A new subspecies of Chlaenius (Chlaeniellus) laeviplaga Chaudoir, 1876, namely Chlaenius (Chlaeniellus) laeviplaga gambronicus ssp. n., is described from South Iran, Hormozgan province. A key for the identification of the subspecies of laeviplaga is provided.